Learning Environment Design for Education Formulation the Future - Taufiqqurrahman, Taufiqqurrahman; Kuswandi, Dedi; Setyosari, Punaji; Ulfa, Saida (JUPE : Jurnal Pendidikan Mandala, 2023)
A survey conducted by Deloitte's recently (in 2023) found data that "As Gen Zs and millennials rethink the role of work in their lives, work/life balance remains a top priority with flexible work arrangements, including part-time jobs growing in popularity". The work-life balance desired by generation Z and generation Alpha should also be accompanied by curriculum preparation that can match the output that should be produced. This research is a literature review, with a descriptive research category with a qualitative approach, this approach was chosen to see and map the potential and symptoms of education in the current information / technology era, this is considered important because our education in the future must be better prepared to play its function as an agent of change, an agent of control, the views of the figures who are the source of literature review in the study are Engku Muhamad Sjafei and Charles M. Reigeluth. 3 recommendations resulting from this literature review 1) a curriculum that focuses on producing graduates who have good qualifications in the fields of soft and hard skills; 2) flexible learning design (hybrid learning) and AI-friendly learning (artificial intelligence). 3) evaluation is seen at the micro level and scale to see the level of understanding of the learners in capturing the material that has been presented.